Upper gastrointestinal lesions in patients with lower extremity peripheral artery disease: data from a retrospective analysis - A. A. Seljanina; A. I. Dolgushina; A. A. Fokin; A. S. Kuznecova; V. V. Genkel' (Кардиоваскулярная терапия и профилактика, 2022)
Aim. To assess the prevalence and structure of upper gastrointestinal (GI) lesions, as well as the factors associated with their development, in patients with lower extremity peripheral artery disease (PAD).Material and methods. This retrospective analysis of medical records with lower extremity PAD includes data from 258 patients. All patients underwent multislice computed tomography angiography of abdominal aortic visceral branches and lower limb arteries, as well as esophagogastroduodenoscopy.Results. Endoscopic evidence of upper GI lesions was detected in 164 (63,6%) patients. In particular, gastroduodenal erosions and ulcers were observed in 57,8% of patients. All patients were divided into two groups: group I — 149 (57,8%) patients with gastroduodenal erosions and ulcers, group II  — 109 (42,2%) patients without it. In group I patients, a higher incidence of mesenteric artery disease was recorded  — 61,7 vs 43,1% (p=0,003). An independent factor associated with the development of gastroduodenal erosions and ulcers in patients with PAD is mesenteric artery disease (relative risk: 4,43; 95% confidence interval: 1,15-17,12 (p=0,031)).Conclusion. In patients with lower extremity PAD, upper GI diseases (63,6%) occur with a high frequency, while gastroduodenal erosions and ulcers was observed in 90,9% of them. The factors associated with the development of erosions and ulcers in patients with lower extremity PAD include mesenteric artery atherosclerosis.